2013
DOI: 10.1007/s11060-013-1226-z
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo mouse model of intraosseous spinal cancer causing evolving paraplegia

Abstract: The spine is the commonest site of skeletal metastatic disease and uncontrolled growth of cancer in the spine will inevitably cause pain and neurologic compromise. Improved understanding of the pathobiology behind this devastating condition is urgently needed. For this reason, the aim of this study was to establish a clinically relevant, animal model of spinal cancer. A percutaneous orthotopic injection of human breast (MDA-MB-231) or human prostate (PC-3) cancer cells was administered into the upper lumbar sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…In current models the clinical evaluation is done by observational findings or by semi-quantitative rating scales (BBB modified scale) after tumor engraftment, progression of paraparesis until paraplegia [30, 40, 41, 5658]. In our model we implemented a quantitative methodology to evaluate gait impairment in tumor implanted rats and demonstrated that stride length, velocity and time in the left hind limbs was affected; in some rats the right hind limb had a compensatory role by supporting more weight during locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…In current models the clinical evaluation is done by observational findings or by semi-quantitative rating scales (BBB modified scale) after tumor engraftment, progression of paraparesis until paraplegia [30, 40, 41, 5658]. In our model we implemented a quantitative methodology to evaluate gait impairment in tumor implanted rats and demonstrated that stride length, velocity and time in the left hind limbs was affected; in some rats the right hind limb had a compensatory role by supporting more weight during locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…Subcutaneous [ 38 ] or orthotopic injections at primary site [ 37 ] were used less frequently. Direct implantation methods include methods to implant tumor cell suspensions [ 34 , 36 ] or tumor pieces harvested from carrier animals [ 24 , 35 ] directly into vertebral structures.…”
Section: Technical Aspects Of Currently Used In Vivo Metastasis Mouse Models With Special Focus On Spine Metastasismentioning
confidence: 99%
“…The direct implantation was carried out in four different ways. Tumor cells were implanted through an anterior transabdominal approach into the vertebral body L3 [ 24 ], through a lateral approach into T10 [ 34 ], through a posterolateral percutaneous route into thoracolumbar junctions [ 36 ] or from posterior into the laminae and spinous process [ 35 ]. To carry out the anterior transabdominal inoculation, Tatsui et al identified the left inferior kidney pole as an orientation mark after an abdominal midline incision in supine position [ 24 ].…”
Section: Technical Aspects Of Currently Used In Vivo Metastasis Mouse Models With Special Focus On Spine Metastasismentioning
confidence: 99%
See 2 more Smart Citations